Interleukin-7 and Immunosenescence - Vanloan Nguyen; Andrew Mendelsohn; James W. Larrick (Journal of Immunology Research)
The age of an individual is an important, independent risk factor for many of the most common diseases afflicting modern societies. Interleukin-7 (IL-7) plays a central, critical role in the homeostasis of the immune system. Recent studies support a critical role for IL-7 in the maintenance of a vigorous healthspan. We describe the role of IL-7 and its receptor in immunosenescence, the aging of the immune system. An understanding of the role that IL-7 plays in aging may permit parsimonious preventative or therapeutic solutions for diverse conditions. Perhaps IL-7 might be used to “tune” the immune system to optimize human healthspan and longevity.